Complete Genome Sequences of Two Novel KPC-2-Producing IncU Multidrug-Resistant Plasmids From International High-Risk Clones of Escherichia coli in China - Wu, Wenhao; Lu, Lingling; Fan, Wenjia; Chen, Chun; Jin, Dazhi; Pan, Hongying; Li, Xi (Frontiers in Microbiology, 2021)
The rapidly increasing prevalence of Klebsiella pneumoniae carbapenemase 2 (KPC-2)-producing bacteria has become a serious challenge to public health. Currently, the blaKPC–2 gene is mainly disseminated through plasmids of different sizes and replicon types. However, the plasmids carrying the blaKPC–2 gene have not been fully characterized. In this study, we report the complete genome sequences of two novel blaKPC–2-harboring incompatibility group U (IncU) plasmids, pEC2341-KPC and pEC2547-KPC, from international high-risk clones of Escherichia coli isolated from Zhejiang, China. Two KPC-2-producing E. coli isolates (EC2341 and EC2547) were collected from clinical samples. Whole-genome sequencing (WGS) analysis indicated that EC2341 and EC2547 belonged to the ST410 and ST131 clones, respectively. S1-nuclease pulsed-field gel electrophoresis (S1-PFGE), Southern blot and conjugation experiments confirmed the presence of the blaKPC–2 gene on the pEC2341-KPC plasmid and that this was a conjugative plasmid, while the blaKPC–2 gene on the pEC2547-KPC plasmid was a non-conjugative plasmid. In addition, plasmid analysis further revealed that the two blaKPC–2-harboring plasmids have a close evolutionary relationship. To the best of our knowledge, this is the first report of E. coli strains carrying the blaKPC–2 gene on IncU plasmids. The emergence of the IncU-type blaKPC–2-positive plasmid highlights further dissemination of blaKPC–2 in Enterobacteriaceae. Therefore, effective measures should be taken immediately to prevent the spread of these blaKPC–2–positive plasmids.